Analysis of myocardial deformation based on pixel tracking in two dimensional echocardiographic images enables quantitative assessment of regional left ventricular function. Issue 8 (30th December 2005) - Becker, M; Bilke, E; Kühl, H; Katoh, M; Kramann, R; Franke, A; Bücker, A; Hanrath, P; Hoffmann, R
Abstract : Objective: To evaluate whether myocardial strain and strain rate calculated from two dimensional echocardiography by automatic frame-by-frame tracking of natural acoustic markers enables objective description of regional left ventricular (LV) function. Methods: In 64 patients parasternal two dimensional echocardiographic views at the apical, mid-ventricular and basal levels were obtained. An automatic frame-by-frame tracking system of natural acoustic echocardiographic markers was used to calculate radial strain, circumferential strain, radial strain rate and circumferential strain rate for each LV segment in a 16 segment model. Cardiac magnetic resonance imaging (cMRI) was performed to define segmental LV function as normokinetic, hypokinetic or akinetic. Results: Image quality was sufficient for adequate strain and strain-rate analysis from two dimensional echocardiographic images obtained from parasternal views in 88% of segments. Obtained radial strain data were highly reproducible and analysis was affected by only small intraobserver (mean 4.4 (SD 1.6)%) and interobserver variabilities (7.3 (2.5)%). Each of the analysed strain and strain-rate parameters was significantly different between segments defined as normokinetic, hypokinetic or akinetic by cMRI (radial strain 36.8 (10.5)%, 24.1 (7.5)% and 13.4 (4.8)%, respectively, p < 0.001). Peak systolic radial strain enabled detection of hypokinesis or akinesis with a sensitivity of 83.5% and a specificity of 83.5% (cut off value 29.1%, receiver operating characteristic (ROC) curve area 0.905, 95% CI 0.883 to 0.923). Peak systolic radial strain analysis also enabled detection of akinesis versus hypokinesis with a sensitivity of 82.7% and a specificity of 94.5% (cut off value 21.0%, ROC curve area 0.946). Peak systolic radial strain-rate analysis was less accurate than peak systolic radial strain analysis to detect cMRI-defined segmental function abnormalities. The accuracy of peak systolic circumferential strain and strain rate was similar to that of corresponding radial parameters. Conclusions: Frame-by-frame tracking of acoustic markers in two dimensional echocardiographic images enables accurate analysis of regional systolic LV function.